2020
DOI: 10.3390/jcm9072256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Evolocumab on Carotid Intima-Media Thickness and Clinical Parameters in Patients Taking a Statin

Abstract: We determined the effects of evolocumab, a fully human monoclonal antibody targeting proprotein convertase subtilisin/kexin type 9, on carotid intima-media thickness (IMT) and the factors associated with the change in carotid IMT in patients taking a statin. The change in carotid mean and maximum IMT before and after the initiation of evolocumab treatment was retrospectively analyzed in 229 statin-treated patients. The changes in clinical parameters, including serum lipid concentrations, were also evaluated. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Not surprisingly, carotid intima-media thickness also did not change in response to alirocumab due to the short treatment period, low sample size, and relatively low baseline intima-media thickness. Over a longer period of 12 months, a recent retrospective observational analysis suggested a reduction of carotid intima-media thickness by evolocumab in 229 patients with statin pre-treatment [ 28 ]. Moreover, carotid intima-media thickness was reduced by treatment with PCSK9-antibodies in addition to ongoing lipoprotein apheresis in only 14 heterozygous familial hypercholesterolemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, carotid intima-media thickness also did not change in response to alirocumab due to the short treatment period, low sample size, and relatively low baseline intima-media thickness. Over a longer period of 12 months, a recent retrospective observational analysis suggested a reduction of carotid intima-media thickness by evolocumab in 229 patients with statin pre-treatment [ 28 ]. Moreover, carotid intima-media thickness was reduced by treatment with PCSK9-antibodies in addition to ongoing lipoprotein apheresis in only 14 heterozygous familial hypercholesterolemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…High PCSK9 concentrations in plasma have been associated with vascular disorders [ 23 , 24 , 25 , 42 , 43 ]. Congruently, pharmacological inhibition of PCSK9 with evolucumab reduced the increase in CIMT along the time in patients treated with statin [ 44 ] and improved the vascular functionality as determined by carotid stiffness in patients with familial hypercholesterolemia [ 45 ]. These observations are in agreement with a rapid reduction of lipid content in carotid plaques achieved with PCSK9 inhibitor alirocumab [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hirai et al. [ 36 ] reported that in patients with hypercholesterolaemia and high CV risk, 12 months of evolocumab reduced the increase in c-IMT in the statin-taking patients. The main disadvantage of their study, however, was that it was retrospective, and they had no control group.…”
Section: Discussionmentioning
confidence: 99%
“…Hirai et al. [ 36 ] reported that the change in triglyceride levels positively correlated with the change in maximum c-IMT during treatment with evolocumab in patients who were already taking statins. They suggested that the effects of evolocumab on c-IMT can be partially explained by the reduction in triglycerides.…”
Section: Discussionmentioning
confidence: 99%